Processing of Heavy Crude Oils - Challenges and Opportunities 2019
DOI: 10.5772/intechopen.82278
|View full text |Cite
|
Sign up to set email alerts
|

PVT Properties of Black Crude Oil

Abstract: Precise PVT studies and behavior of phase-equilibrium of petroleum reservoir fluids are essential for describing these fluids and appraising their volumetric behavior at several pressure stages. There are numerous laboratory studies that can be performed on a reservoir sample. The amount of data desired determines the number of tests to be performed in the laboratory. Generally, there are three laboratory tests which characterize hydrocarbon fluids, namely primary study, constant mass depletion, and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The oil phase can be described by several correlations depending on the type of crude. For instance, the correlation of Al-Marhoun is adopted for Middle East crude oils, highlighting a trend for locally defined formulations . Surfactants locate at the O/W interface, a process described as adsorption.…”
Section: Physical Properties Of Emulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil phase can be described by several correlations depending on the type of crude. For instance, the correlation of Al-Marhoun is adopted for Middle East crude oils, highlighting a trend for locally defined formulations . Surfactants locate at the O/W interface, a process described as adsorption.…”
Section: Physical Properties Of Emulsionsmentioning
confidence: 99%
“…For instance, the correlation of Al-Marhoun 157 is adopted for Middle East crude oils, highlighting a trend for locally defined formulations. 158 Surfactants locate at the O/W interface, a process described as adsorption. To treat surfactant adsorption, the second law of thermodynamics can be applied.…”
Section: Physical Properties Of Emulsionsmentioning
confidence: 99%
“…This can be attributed to crude oil containing predominantly acidic polar fractions (evident from TAN, and SARA analysis given in Table ). It is well known that polar compounds have profound effects on rock wettability in a carbonate formation, particularly the acidic components, which help the oil blobs adhere to the positively charged calcite surface, rendering them oil-wet. , Dodecane being void of any polarity is expected to have a lesser tendency to attach to the calcite surface. The 50:50 crude/dodecane results were in between the two extremes.…”
Section: Resultsmentioning
confidence: 99%
“…Inaccuracies in reservoir fluid characterization will result in errors in field development planning, uncertainty in the estimated prediction of oil and gas recovery, and thus in the overall asset value. It has been reported that one of the foremost methods of characterizing and predicting the behavior of reservoir fluids is the Pressure-Volume-Temperature (PVT) analysis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Reservoir fluid Pressure-Volume-Temperature (PVT) empirical methods are quite expensive [3][4][5][6]; hence correlations have been developed to obtain these PVT properties. These correlations are highly region-dependent and rarely work well in different regions since they were developed with data from particular regions.…”
Section: Introductionmentioning
confidence: 99%